Precise modulation strategies of 2D/3D perovskite heterojunctions in efficient and stable solar cells. Issue 28 (15th March 2023) - Zhou, Qian; Liu, Baibai; Shai, Xuxia; Li, Yuelong; He, Peng; Yu, Hua; Chen, Cong; Xu, Zong-Xiang; Wei, Dong; Chen, Jiangzhao
Abstract : We summarize various effective methods for controlling the film thickness and structural phases in 2D/3D perovskite heterojunction structures and discuss possible solutions to improve the performance of perovskite devices. Abstract : 2D/3D perovskite heterojunctions exhibit promising prospects in the improvement of efficiency and stability of perovskite solar cells (PSCs). However, many challenges remain in the development of high-quality 2D/3D heterojunctions, such as a reliable pathway to control the perovskite phase and generally poor performance in inverted (p–i–n) devices, which limit their commercialization. Fortunately, many excellent works have proposed lots of strategies to solve these challenges, which have triggered a new wave of research on 2D/3D perovskite heterojunctions in recent years. In this paper, the latest research progress and the critical factors involved in the modulating mechanisms of PSCs with 2D/3D heterojunctions have been summarized and laid out systematically. The advantages of constructing 2D/3D perovskite heterojunctions in PSCs are highlighted, and the problems and related solutions of low-dimensional perovskites as passivation layers towards high-performance PSCs are also discussed in depth. Finally, the prospects of 2D/3D perovskite heterojunctions utilized in the passivation strategies to further improve the photovoltaic performance of PSCs in the future have been presented.